O conhecimento de escolares do ensino fundamental sobre as modalidades do atletismo - Diogo Dias de Souza (Sociedade Brasileira de Pediatria, 2022)
School physical education is essential for the development of children and adolescents, and through daily activities, they begin to develop their motor and physical skills. The knowledge of athletics modalities by elementary school students became the object of this study due to the possibility of contributing to a better physical preparation of students. Through a transversal and exploratory design, in a convenience sample consisting of 30 students, a questionnaire prepared by the author was applied. It was observed that the preferred sport was running for 60% of respondents. Results regarding the other variables analyzed suggested that, even today, there is a need for physical education teachers to place a greater emphasis on athletics and its modalities, aware of the relevant benefits that regular practice can bring to growing and developing children and adolescents.